The influence of self-concept and peer support on social anxiety of stutter survivors in Indonesia - Nanda Faj'riah Azzari; Lely Ika Mariyati; Dwi Nastiti (Jurnal Psikologi Terapan dan Pendidikan, 2023)
Stuttering is a speech disorder characterized by repeating sounds, syllables, or prolonging sounds. Individuals with a stutter know precisely what they want to say but have difficulty producing a regular flow of speech. Stuttering, which may be accompanied by behaviors such as rapid eye blinking or lip trembling. This study aims to determine the relationship between self-concept and peer support with social anxiety in stutter survivors in the Indonesia Stuttering Community. The sample for this study was 209 members of the Indonesia Stuttering Community out of a population 0f 537 members. The sample was selected using a purposive sampling technique with criteria of individual who have speech disorders (stuttering) and are part of the ISC community. Data collection uses three psychological scale, namely self-concept scale, peer support scale and social anxiety scale. The result of this study indicate that the effective contribution value is 46.1%, It can be concluded that there is an influence betweet self-concept and peer support on social anxiety among stuttering survivors who are part of the ISC community.